Correlation between thrombocytopenia and host response in severe fever with thrombocytopenia syndrome. - Xiao-Kun Li; Ke Dai; Zhen-Dong Yang; Chun Yuan; Ning Cui; Shao-Fei Zhang; Yuan-Yuan Hu; Zhi-Bo Wang; Dong Miao; Pan-He Zhang; Hao Li; Xiao-Ai Zhang; et al. (Public Library of Science (PLoS), 2020)
Severe Fever with Thrombocytopenia Syndrome (SFTS) is an emerging infectious disease caused by a novel bunyavirus, SFTS virus (SFTSV), with fatal outcome developed in approximately 17% of the cases. Thrombocytopenia is a hallmark feature of SFTS, and associated with a higher risk of fatal outcome, however, the pathophysiological involvement of platelet in the clinical outcome of SFTS remained under-investigated. In the current study, by retrospectively analyzing 1538 confirmed SFTS patients, we observed that thrombocytopenia was associated with enhanced activation of the cytokine network and the vascular endothelium, also with a disturbed coagulation response. The platelet phenotypes were also extensively altered in the process of thrombocytopenia development of SFTS patients. More importantly, all these disturbed host responses were related to the severity of thrombocytopenia, thus were considered to play in a synergistic way to influence the disease outcome. Moreover, the clinical effect of platelet transfusion was assessed by comparing two groups of patients with or without receiving this therapy. As a result, we observed no therapy effect in altering frequencies of fatal outcome, clinical bleeding development, or dynamic change of platelet count during the hospitalization. It's suggested that platelet supplementation alone acted a minor role in improving disease outcome, therefore new therapeutic intervention to regulate host response should be proposed. The current results revealed some evidence of interrelationship between platelet count and clinical outcome of SFTS disease from the perspective of activation of the cytokine network, the vascular endothelium, and the coagulation/fibrinolysis system. These evaluations might help to attain a better understanding of the pathogenesis and therapy choice in SFTS.